Theory Of Islamic Education, Philosophy And Curriculum At Tertiary Level - Ridwan M Daud (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
This paper explores the foundations and principles of Islamic education, drawing from the Qur'an, Sunnah, and insights from esteemed Muslim scholars. It delves into the pivotal concepts of ta'lim, tarbiyah, and ta'dib, elucidating their roles within the framework of Islamic education. Islamic education centers on two core tenets: the acquisition of knowledge and the purification of the self. It aims to instill Islamic ideals, fostering purity, justice, and societal harmony. The objectives of Islamic education encompass the acquisition and dissemination of knowledge, the cultivation of moral values, and the pursuit of knowledge for societal welfare, all with a focus on pleasing Allah. These objectives cater to individual capacities, nurturing well-rounded personalities for community enrichment. Moreover, the paper outlines the aims of teaching Islamic religious studies, emphasizing faith comprehension and ethical conduct to prepare individuals for the Hereafter while guiding their actions in the present. The curriculum of Islamic education integrates language studies, natural sciences, history, and religious studies, intertwining them with fundamental principles such as acknowledging Allah's Oneness, comprehending prophetic missions, anticipating the Day of Judgment, and assuming vicegerency on Earth. Drawing from influential reformists, it highlights education's crucial role in reforming Muslim societies, advocating for a balanced approach that blends acquired and revealed knowledge across educational institutions